Xeroderma Pigmentosum: Man Deprived of His Right to Light - Subhash Mareddy; Jithendra Reddy; Subhas Babu; Preethi Balan (The Scientific World Journal)
Xeroderma pigmentosum (XP) is a hereditary autosomal recessive disorder characterized by photo hypersensitivity of sun exposed tissues and subsequent several-fold increased risk for malignant changes resulting from impaired ability to repair UV-induced DNA damage. Estimated incidences vary from 1 in 20,000 in Japan to 1 in 250,000 in the USA, and approximately 2.3 per million live births in Western Europe. Diagnosis is made clinically by the presence of unusual sunburns or lentiginosis or onset of cancers at an early age. It is confirmed by cellular tests for defective DNA repair. Although there is no cure for XP as of now, skin problems can be ameliorated with the use of sunscreens, sun avoidance methods, and recurrent tumor excisions. Oral isotretinoin and topical application of 5-fluorouracil to treat actinic keratoses are other therapeutic options. T4N5 and photolyase liposomal lotions are innovations in the therapy of XP. Genetic counselling implicating the effect of consanguineous marriages should be considered in the management of XP patients.